Raul Lino and the City - Pereira, Paulo Manta (Preprints, 2019)
Over a period of nearly one hundred years, Raul Lino da Silva (1879-1974) experienced the profound political, social and economic changes that marked the twentieth century in Portugal. Having been born during the Constitutional Monarchy (1822-1910), he lived through the First Republic (1910-1926), the Military Dictatorship (1926-1933) and the Second Republic, or Estado Novo (New State, 1933-1974), and died shortly after the Carnation Revolution of 25 April 1974, at the dawning of the Third Republic. Raul Lino was the architect who published the most in Portugal, having become known through his advocacy of the “Campanha da casa portuguesa” (“Portuguese house campaign”), which provoked a great deal of controversy among his peers. He is less known for the transversal quality of his synthesis between architecture, the decorative arts and territory, and its underlying affirmation of an idea of the city, which we conjecture from a diagonal reading of his theoretical and plastic narrative. We limit the analysis to the first half of the 20th century, concentrating on ten case studies, that encompass architectural projects, urbanistic plans and reports. The above expound the broad conception which he defended in the same year as was held the First National Architecture Congress (1948), whose proposals ratified in Portugal the orthodoxy established in 1933 by the International Congresses of Modern Architecture (CIAM). Quoting Aristotle Raul Lino conceived the city as the locus of happiness, shaping the possibilities of consensus between tradition and modernity by means of architecture, which is both envelope and stage for our collective existence. In fact, Raul Lino anticipated themes to be found in the narratives of authors like Aldo Rossi (1966), Paul Virilio (2004, 2009) or Peter Zumthor (2006), and his thought proves particularly relevant and timely in the present day.